Ministerial Careers and Accountability in the Australian Commonwealth Government - Dowding, Keith (ANU Press, 2012)
This book examines the roles, responsibilities and accountabilities of Australian cabinet ministers. It examines the sorts of jobs ministers do, what is expected of them, what they expect of the job and how they (are supposed to) work together as a team. It considers aspects of how they are chosen to become ministers; how they are scrutinised by parliament and the media; and how ministers themselves view accountability. It also looks at the causes of calls for ministers to resign, examines scandals around ministers and assesses ministerial accountability.